On range and response : dimensions of process flexibility - Chou, Mabel C. (2015)
There are two dimensions to process flexibility: range versus response. Range is the extent to which a system can adapt, while response is the rate at which the system can adapt. Although both dimensions are important, the existing literature does not analytically examine the response dimension vis-a-vis the range dimension.